2022
DOI: 10.3390/nano12193427
|View full text |Cite
|
Sign up to set email alerts
|

Production of Minor Ginsenoside CK from Major Ginsenosides by Biotransformation and Its Advances in Targeted Delivery to Tumor Tissues Using Nanoformulations

Abstract: For over 2000 years, ginseng (roots of Panax ginseng C.A. Meyer) has been used as a traditional herbal medicine. Ginsenosides are bioactive compounds present in ginseng responsible for the pharmacological effects and curing various acute diseases as well as chronic diseases including cardiovascular disease, cancer and diabetes. Structurally, ginsenosides consist of a hydrophobic aglycone moiety fused with one to four hydrophilic glycoside moieties. Based on the position of sugar units and their abundance, gins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 134 publications
0
10
0
Order By: Relevance
“…Ginsenosides. Ginsenosides (GSs) are a group of ginseng-derived compounds 179 with bioactivities against diabetes, cancer, depression, cerebral ischemia, endothelial cell injury, and cardiovascular diseases among others. 180 Ginsenosides are used extensively in the development of anticancer drugs given that they have been shown to reduce multidrug resistance and improve the anti-tumor effect through synergy with other drugs.…”
Section: Reviewmentioning
confidence: 99%
“…Ginsenosides. Ginsenosides (GSs) are a group of ginseng-derived compounds 179 with bioactivities against diabetes, cancer, depression, cerebral ischemia, endothelial cell injury, and cardiovascular diseases among others. 180 Ginsenosides are used extensively in the development of anticancer drugs given that they have been shown to reduce multidrug resistance and improve the anti-tumor effect through synergy with other drugs.…”
Section: Reviewmentioning
confidence: 99%
“…The identification and isolation of bacterial endophytes from P. ginseng and P. notoginseng have provided novel sources of both major and minor ginsenosides, with the latter based on β-glucosidase activity [ 9 ]. The major goals in practical application are mass production and nanoparticle preparation of minor ginsenosides with large pharmacological effects [ 96 , 97 ]. Novel forms of minor ginsenosides may have enormous promise as therapeutic agents [ 96 ].…”
Section: Potential Application Of β-Glucosidases and Converted Ginsen...mentioning
confidence: 99%
“…Novel forms of minor ginsenosides may have enormous promise as therapeutic agents [ 96 ]. Functionalization or loading of minor ginsenosides onto biocompatible polymers and nanoformulations improved the solubilization and absorption of ginsenosides for clinical applications such as cancer therapy [ 97 ].…”
Section: Potential Application Of β-Glucosidases and Converted Ginsen...mentioning
confidence: 99%
“…( P. ginseng ) is a traditional herb, the main ingredient of which is ginsenoside. Among many ginsenoside monomers, ginsenoside CK is a rare ginsenoside transformed from ginsenoside Rb1 (Jiang et al., 2021; Murugesan et al., 2022). Previous studies have shown that ginsenoside Rb1 can improve hair loss (Jeong et al., 2022; Shin et al., 2014; Zhang et al., 2019; Zheng et al., 2013).…”
Section: Introductionmentioning
confidence: 99%